Fostering land-sharing scheme as alternative resettlement to the inevitable Old Fadama evictions and challenges in Ghana. Issue 4 (2nd October 2022) - Mensah, Francis; Yu, Qingnian; Shi, Guoqing
ABSTRACT: The study aims to explain the essence of an alternative approach to the Old Fadama inevitable eviction and to justify the merits & feasibility of a land-sharing scheme to the community. Previous studies used principles to explain the feasibility of land-sharing, but the present study adopted both principles and theories. The injustice and social inequality from evictions are ironed out by applying Amartya Sen's idea on justice that counters transcendentalism theory. The study answers three critical questions: why the community residents demand justice, how advantageous land-sharing is to other methods, and how feasible land-sharing is to the research area. A survey was done in the study area using structured questionnaires, interviews, and observations. A purposive sampling technique selected 600 affected community residents, 30 local government officials, and one coordinator from Amnesty International Ghana. Both qualitative and quantitative analytical methods were used to analyse the primary data. First of all, the study findings revealed four substantive claims for requesting justice from the local authorities; citizenship rights, property rights, temporal permit, and long-term stay. Secondly, land-sharing is preferred to relocation and cash compensation because it poses less risk than the other two. Finally, the study supported the feasibility of a land-sharing scheme to the Old Fadama based on Rabé's (2005) principles. The study also concluded that information and compensation are critical to the resettlement process; hence, local authorities should.